A prospective study on the efficiency of ciprofloxacin in combination with chloramphenicol and probiotics against multiple antibiotics resistant Klebsiella pneumoniae - Ahmed, Akash (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2017.